Real-Time 3-Dimensional Transesophageal Echocardiography Imaging–Guided Percutaneous Closure of Left Ventricular to Left Atrial Fistula. Issue 12 (15th December 2019) - Baribeau, Yanick; Mahmood, Faraz; Sharkey, Aidan; Bortman, Jeffrey; Matyal, Robina; Laham, Roger; Mahmood, Feroze
Abstract : Supplemental Digital Content is available in the text.